Application of Molecular Biology for Identification of Virus Resistance Gene in Melon - Budi Setiadi Daryono (Indonesian Journal of Biotechnology, 2015)
Source of resistance to an Indonesia isolate of Cucumber mosaic virus (CMV-B2) in melon cultivar Yamatouri has been reported. Moreover, Creb-2, a locus that confers resistance to CMV-B2 in Yamatouri has been determined as a single dominant gene. To elucidate the resistance mechanism conferred by Creb-2 in more detail, it is necessary to clone the Creb-2 gene and determine its molecular structure. One approach is by amplification and cloning of melon resistance gene analogs (MRGAs) based on degenerated PCR primers designed from conserved amino acids in the NBS-LRR motifs (P-loop, Kinase-2, and the GLPL) and Toll/ Interleukin-1 receptor-like region (TIR). This study was aimed to identify and characterize the resistance gene analogs from Cucumis melo L. cv. Yamatouri by employing polymerase chain reactions (PCR) as a molecular biology tools with degenerate primers based on conserved motifs of cloned R genes. The application of molecular biology such as DNA isolation, degenerate primers and PCR condition, cloning, sequencing, linkage analysis and mapping of resistance gene analogs to Creb-2 gene in melon will be widely discussed in this paper